MITIGASI BENCANA DI KAWASAN RAWAN BENCANA (KRB) III GUNUNG MERAPI - , FADRI MUSTOFA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kalitengah Lor village communities, Kalitengah Kidul and Srunen a settled community in Disaster Prone Areas (KRB) III Mount Merapi. After the eruption of Mount Merapi in 2010, the government issued relocation policy for the people who settled in Disaster Prone Areas (KRB) III Mount Merapi. However, the public rejects the policy. Because, people assess the slopes of Mount Merapi as a source of livelihood. In addition, people judge the distance fixed residential locations with slopes too much, which is 15 kilometers so that it can hamper the sustainability of life. This study aims to understand the disaster mitigation efforts in Hamlet Kalitengah Lor, Kalitengah Kidul and Srunen, Glagaharjo Village, Cangkringan, Sleman District including Disaster Prone Areas (KRB) III Mount Merapi. The method used in this study is a qualitative method with a case study approach. Observation, in-depth interviews, and documentation is the means used in this study to collect data. Furthermore, the analysis and conclusion in this study rests on the understanding that disaster mitigation is part of disaster management. Disaster mitigation is divided into two kinds, namely structural and non-structural mitigation. Structural mitigation is disaster reduction through physical approaches, such as the development of early warning systems. Meanwhile, non-structural mitigation is disaster reduction through non-physical approaches, such as disaster preparedness training. The results of this study indicate mitigation performed by several actors. Based on the stakeholder analysis, the Regional Disaster Management Agency (BPBD) Sleman district has a level of power and a high interest in disaster mitigation efforts. This is indicated by the disaster mitigation efforts that include structural and non-structural mitigation. For example, disaster preparedness training and development of early warning systems. Meanwhile, the local community and the Institute of Non Government Community Architect (ARKOM) and Yogyakarta Indonesian Environmental Forum (WALHI) Yogyakarta has a low level of power, but has a high level of importance. This is indicated by the disaster mitigation efforts tend to be non-structural. For example, disaster preparedness training, the establishment of the Disaster Risk Penurangan (DRR), disaster preparedness and savings programs jimpitan disaster preparedness. Thus, the need for cooperation among actors in the disaster mitigation efforts, through coordination and communication on a regular basis. Furthermore, the need for the division of tasks between the actors involved in the disaster mitigation efforts. Thus, the mitigation can be run effectively and efficiently.